Process of Commercialization of Agriculture in Amhara Region-Ethiopia: Prospects and Constrains (Global Journal of Science Frontier Research, 2017)
The growth in total output and productivity in the last fifteen years in the Amhara region are not accompanied by significant changes in the marketed surplus of cereal crops. The use of improved seeds and biological and chemical inputs have increased; but not at the rate required to commercialize the agriculture to produce high marketed surplus. For instance, the proportion of grain marketed was 19.65 percent in 2001/2 and it was 20.3 percent in 2009/10.In the case of cereals, the proportion of output marketed has increased marginally from 12.99 percent to 15.2 percent during this period. The proportion of pulses marketed has increased from 18.66 percent to about 23 percent. The proportion of oilseeds marketed has declined to 45.77 percent in 2009/10 compared to 49.36 percent. The farm technology is still predominantly traditional. The percentage of acreage of grain crops in the total acreage has come down in the past fifteen years. Small farmers’ market orientation is seen in terms of increase in the acreage allotted for pulses, oilseeds, vegetables, sugarcane, coffee and chats. What is required is big push for creating infrastructure like dams or drainage system to accelerate the process of commercialization of agriculture in the region. Input markets must be reformed to enable private, public agencies and cooperatives to act competitively to provide needed agriculture inputs such as improved seeds, biological and chemical inputs to the farmers so as to reach higher level of yield and output. The significant proportion of crop land is used for cereal crops perpetuating subsistence farming. There is persistence of integrated farming. Diversification of crops is seen on the larger size of holdings.